Chemical and sensory composition of arabica and robusta coffee in response to modifications in the roasting process - Freitas, Valdeir Viana (2023)
In recent years, the coffee market has experienced remarkable growth, driven by its expansion and production on a global scale. South America, in particular, stands out as one of the main coffee-producing regions, led by Brazil, and is also the largest exporter of this agricultural commodity. Furthermore, it is relevant to emphasize that coffee is one of the most widely consumed beverages worldwide, attracting an increasingly discerning consumer audience regarding product quality. An essential element in the process of transforming green coffee beans into an aromatic and flavorful cup of coffee is the roasting stage. This operation plays a fundamental role in creating the distinctive flavors and aromas found in the final beverage. In this context, the purpose of this study was to investigate the complexity of roasting by conducting a thorough analysis of the physicochemical and sensory changes that occur during this process. For this purpose, six different roasting profiles were employed, where temperature and roasting time were carefully considered and adjusted. The results unveiled intriguing information. It was found that the highest levels of total phenolics, compounds endowed with beneficial antioxidant properties for health, were identified in coffees subjected to specific temperatures, such as 135 °C/20.20 min and 210 °C/9.02 min. These findings not only provide valuable insight into the nutritional profile of roasted coffee but also emphasize the influence of different roasting profiles on these characteristics. Surprisingly, C. canephora, known for its more robust and full-bodied character, exhibited superior antioxidant activity compared to C. arabica in many of the evaluated roasting profiles. This finding may redefine the traditional view that C. arabica always surpasses C. canephora in terms of quality. The results showed that roasting profiles, as well as the species, strongly influenced all investigated parameters, particularly the concentration of sugars, organic acids, and melanoidins. Succinic acid was the organic compound with the highest concentrations, with the highest concentration observed in C. canephora at 210 °C/11.01 min (224.24 mg/g), with the highest concentrations of organic acids found in this same roasting profile and species (430.39 mg/g). Fructose was the sugar with the highest concentration, particularly in the 210 °C/11.01 min roast, which exhibited 17.14 mg/g. The highest melanoidin content was also found in this same roasting profile and species. Sensory evaluation, conducted by both experts and consumers, has revealed significant differences in flavor, aroma, and overall quality properties among coffee varieties and various roasting profiles. C. arabica has received higher ratings compared to C. canephora, particularly with better scores for roasting profiles at 135 °C/20.20 min and 230 °C/17.43 min. These conclusions offer a deeper understanding of the nuances present in the roasting process and its impact on the coffee experience for enthusiasts of this beverage. Therefore, as we delve deeper into the coffee market, it becomes evident that roasting represents an operation that not only transforms the beans but also influences flavor, nutritional value, and consumer perception. Keywords: Coffea arabica L. Coffea canephora. Roasting. Chemical composition. Coffee quality.